Frequency of Cognitive Decline in Asthma Patients and Associated Socio-Demographic Factors - Satti, Raja Rizwan Ul haq; Rasheed, Syed Abdul; Gul, Rubab; Athar, Muhammad Hammad (Pakistan Armed Forces Medical Journal, 2022)
Objective: To look for the relationship of various factors along with frequency of decline in cognition among the patients suffering from asthma. Study Design: Cross sectional study. Place and Duration of Study: Medicine department, Pak Emirates Military Hospital Rawalpindi Pakistan, from Aug to Oct 2018. Methodology: One hundred and thirty-five asthma patients with duration of illness for more than a year evaluated by classified medical specialist or pulmonologist were recruited in this study. Decline in the cognition was recorded by the help of the British Columbia Cognitive Complaints Inventory (BC-CCI). Various socio-demographic factors were also correlated with the decline in cognition among these patients suffering from asthma. Results: Out of 135 patients of asthma, 68 (50.4%) patients did not show any decline in cognition, 45 (33.3%) patients showed mild decline, 16 (11.8%) patients had moderate while 06 (4.4%) patients had severe cognitive decline on this screening instrument. Mean age of the patients participating in this study was 40.64 ± 3.12 years. Mean duration of illness among these patients of asthma was 5.29 ± 3.58 years. Use of more than one pharmacological agent for control of asthma and longer duration of asthma were significantly correlated with the presence of decline in cognition among the patients suffering from asthma (p-value <0.05). Conclusion: High risk patients for cognitive decline in our study were patients with long standing asthma or those using multiple medications for the control of asthma. Decline in cognitive ability emerged as a significant problem in the asthmatics who have .........